Roots of hate: Anti-semitism in Europe before the Holocaust - Brustein, William (Cambridge University, 2013)
On the eve of the Holocaust, antipathy toward Europe's Jews reached epidemic proportions. Jews fleeing Nazi Germany's increasingly anti-Semitic measures encountered closed doors everywhere they turned. Why had enmity toward European Jewry reached such extreme heights? How did the levels of anti-Semitism in the 1930s compare to those of earlier decades? For example, were Germans more anti-Semitic than their European neighbors, and, if so, why? How does anti-Semitism differ from other forms of religious, racial, and ethnic prejudice?" "In pursuit of answers to these questions, William I. Brustein offers the first truly systematic comparative and empirical examination of anti-Semitism in Europe before the Holocaust. Brustein proposes that European anti-Semitism flowed from religious, racial, economic, and political roots, which became enflamed by economic distress, rising Jewish immigration, and socialist success. To support his arguments, Brustein draws upon a careful and extensive examination of the annual volumes of the American Jewish Year Book and more than forty years of newspaper reportage from Europe's major dailies. The findings of this informative book offer a fresh perspective on the roots of society's longest hatred.